Procrastination in the early detection of breast cancer - Cleoneide Paulo Oliveira Pinheiro; Raimunda Magalhães da Silva; Christina César Praça Brasil; Indara Cavalcante Bezerra; Ana Nery Melo Cavalcante; Aimêe Veras Alexandre; Cleciana Alves Cruz (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to analyze the meaning of postponement of breast cancer detection based on interviews with 26 women who were submited to mastectomy. Method: qualitative study based on Symbolic Interactionism with Content Analysis in thematic modality, carried out in a public service outpatient clinic, in a capital city of Northeastern Brazil. Results: faced with the participants' reports, the theme 'meanings attributed to procrastination of breast health care' emerged. The meaning given by women to the reasons for postponing breast care permeate the interfaces between personal reasons and difficulties found in the healthcare network. Final considerations: early detection is considered to be delayed for fear of diagnosis, personal, cultural barriers, and difficulties in health services.